Avaliação imunoistoquímica das galectinas -1, -3 e -7 em carcinoma epidermóide de lábio - Almeida, Maria Manuela Rodrigues de Lemos (2014)
The oral cancer is a major cause of morbidity and mortality worldwide. In Brazil, 15,000 new cases are expected for the year 2014. Lip squamous cell carcinoma features are similar to skin lesions and have as main etiological agent, the chronic sun exposure. The galectins -1, -3 and -7 are proteins involved in tumorigenesis and have been investigated due to changes in their expressions in oral cancer. The objective of this study was to evaluate the expression by Immunohistochemistry of galectins-1, -3 and -7 in 30 cases of lip squamous cell carcinoma, making the correlation with clinical data, histological grading of malignancy through the proposed systems for Bryne (1998) and WHO (2005). The parameters analyzed and expression of galectins -1, -3 and -7 were subjected to statistical analysis (Chi-square, Fisher exact test and test for comparison of Binomial proportions). There was no expression of galectin -1 in 93.3% of cases, showing statistically significant correlation (p = 0.0356) between histological grading of malignancy proposal by WHO and the marked cell type. There was no statistically significant correlation between the galectin -3 with none of the evaluated parameters. Expression of galectin-7 was present in all cases evaluated and showed statistical significance between the marked cell type and regional metastasis (p=0,0000) and between the marked cell type and histological grading proposal for Bryne. Changes in the expression of galectinas -1, -3 and -7 suggest the participation of these proteins in carcinogenesis. We conclude, through the results of this research, that the expression of these proteins in squamous cell carcinoma of lip can act as a marker of biological behaviour of this type of lesion.